Factibilidad de una micro empresa procesadora de bebida fermentada (vino) de mandarina (citrus reticulata) en el cantón Bolívar - Vinces Zambrano, Luis Andrés (2019)
The objective of the research was to determine the feasibility of a microenterprise processing fermented mandarin drink (citrus reticulata) in Bolívar canton. Through the market study, it was possible to identify that the acceptance of the product is 26% and that the potential consumers oscillate between 18-70 years, middle class, medium-high and high, willing to acquire mandarin wine, with a demand annual of 19.362 liters. The resources needed to start up the microenterprise are made up of materials, human talent, tools, and infrastructure, whose total investment value is 74.190,20 dollars. Besides, with the Leopold Matrix applied in the environmental study, very low adversity impacts were estimated, where the adequacy of the terrain, followed by the automotive transport, are the environmental aspects that will have negative repercussions. Through the economic-financial study, it was determined that the project is profitable and viable, with a net present value (NPV) of 85.175,13 dollars, an internal rate of return (IRR) of 20%, and a beneficial cost of 1.15 dollars. Which means that for every dollar invested you get fifteen cents of profit.